NYPD Red 2 - Patterson, James, 1947-; Karp, Marshall (New York : Vision, 2015)
NYPD Red Detective Zach Jordan and his partner Kylie MacDonald are put on the case when a woman of vast wealth and even greater connections disappears. Zach and Kylie have to find what's really behind this murderer's rampage while political and personal secrets of the highest order hang in the balance.
Accelerated Reader AR
Keywords: Detective and mystery stories -- New York (State) -- New York; Murder -- Investigation -- New York (State) -- New York -- Fiction; Motion pictures -- Production and direction -- New York (State) -- New York -- Fiction; Suspense fiction